Pluto! : not a planet? not a problem! - McAnulty, Stacy (McAnulty, Stacy. Our universe., 2023)
"Hot diggity dog! Meet Pluto! The runt of a litter of eight planets. Pluto may not be the biggest or fastest planet to revolve around the Sun, but it has a unique story to tell. From the tale of how it was found by humans to its naming as a dwarf planet, it's Pluto's turn to take the spotlight and properly re-introduce itself."--Publisher marketing